(untitled) (Editora Impacto Científico, 2025)
Emotional trauma has emerged as a potent biological modulator capable of inducing long-lasting alterations in neuroendocrine and immune homeostasis. Epigenetics, as the interface between the environment and the genome, reveals that traumatic experiences can trigger stable modifications in DNA methylation patterns, histone acetylation, and microRNA regulation without altering the genetic sequence. Recent evidence demonstrates that exposure to severe stressors disrupts the regulation of the hypothalamic-pituitary-adrenal (HPA) axis, particularly through hyper- or hypomethylation of genes such as NR3C1 and FKBP5, impairing cortisol negative feedback and neuronal plasticity. These mechanisms not only sustain persistent hypersensitivity to stress but also suggest potential transgenerational effects mediated by germ cells or maternal environments during embryonic development. Understanding these epigenetic dynamics offers new therapeutic and predictive perspectives for trauma-related psychiatric disorders, underscoring the importance of integrating molecular neuroscience, psychology, and translational medicine. DOI: https://doi.org/10.56238/edimpacto2025.090-051